2008
DOI: 10.1098/rstb.2007.2242
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of nervous system centralization

Abstract: It is yet unknown when and in what form the central nervous system in Bilateria first came into place and how it further evolved in the different bilaterian phyla. To find out, a series of recent molecular studies have compared neurodevelopment in slow-evolving deuterostome and protostome invertebrates, such as the enteropneust hemichordate Saccoglossus and the polychaete annelid Platynereis. These studies focus on the spatially different activation and, when accessible, function of genes that set up the molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
150
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(163 citation statements)
references
References 49 publications
9
150
0
1
Order By: Relevance
“…The floor plate corresponds to the vertebrate CNS dorsal midline and is thought to be homologous to the Platynereis ventral midline 13,14 , therefore pointing out a deep evolutionary conservation of the expression of wnt4 genes in bilaterians. However, floor plate-secreted Wnt4 proteins are not involved in the control of cell proliferation and differentiation in the vertebrate neural tube and instead have been shown to control the antero-posterior guidance of commissural axons 50 , as well as some other unrelated processes such as segmental patterning 51 and midline convergence of organ primordia 52 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The floor plate corresponds to the vertebrate CNS dorsal midline and is thought to be homologous to the Platynereis ventral midline 13,14 , therefore pointing out a deep evolutionary conservation of the expression of wnt4 genes in bilaterians. However, floor plate-secreted Wnt4 proteins are not involved in the control of cell proliferation and differentiation in the vertebrate neural tube and instead have been shown to control the antero-posterior guidance of commissural axons 50 , as well as some other unrelated processes such as segmental patterning 51 and midline convergence of organ primordia 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, the annelid P. dumerilii has become a valuable model for evolutionary developmental biology studies, especially regarding the development of its nervous system that resembles that of vertebrates in many aspects. Studies in Platynereis shed light on several ancestral features of the CNS in bilaterians 13 , including the molecular regionalization of the neurectoderm along the mediolateral axis 14 , the presence of conserved brain neurosecretory cells 15 , and the common ancestry of the vertebrate pallium and the protostome corpora pedunculata 16 .…”
mentioning
confidence: 99%
“…More recent studies, particularly comparisons between the annelid Platyneris and Saccoglassus, have revealed a more complex situation. Arendt et al (2008) illustrate the conservation of the mediolateral patterning of the neurectoderm, as well as a conservation of neuron types, suggesting a 'conservation of molecular architectures ' (p. 1527). But can we infer ancestral morphologies from these conserved architectures?…”
Section: *Erwind@siedumentioning
confidence: 98%
“…The complexity of this toolkit varies as new studies and broader comparative studies are reported, but minimally includes the following: anterior/posterior (A/P) patterning with seven or eight HOX genes (de Rosa et al 1999;Balavoine et al 2002), and the associated microRNA responsible for inhibiting translation of HOX mRNAs (de Robertis 2008); the HOX genes part of a larger super cluster of at least eight other ANTP-class genes including the ParaHox and NK cluster genes (Butts et al 2008); dorsal/ventral (D/V) patterning controlled by the sog/chordin dpp/ BMP2/4 system (Arendt & Nubler-Jung 1994;De Robertis & Sasai 1996); anterior patterning via ems/ Emx and otd/Otx and a tripartite brain (Arendt & Nubler-Jung 1999;Reichert & Simeone 2001;Arendt et al 2008) with posterior patterning via evenskipped/evx and caudal/cdx; segmentation through engrailed and Delta -Notch (Holland et al 1997;Balavoine & Adoutte 2003;Stollenwerk et al 2003;Tautz 2004); eye formation controlled by a dense network of genes, including Pax6 and ey (Quiring et al 1994;Halder et al 1995;Gehring 2004), but see Arendt et al (2004) and Fernald (2000); endoderm formation and a regionalized through gut via GATA transcription factors, brachyury and goosecoid (Arendt et al 2001); heart formation via Nkx2.5/tinman (Harvey 1996;Bodmer & Venkatesh 1998;Olson 2006); and distal-less involvement in appendage formation (Panganiban et al 1997;Panganiban & Rubenstein 2002;Pueyo & Couso 2005). The pattern of acquisition of microRNAs tracks increasing morphological complexity and provides important information on the evolution of developmental control (Sempere et al 2006;Gimson et al 2008;Wheeler et al 2009).…”
Section: *Erwind@siedumentioning
confidence: 99%
“…One consequence of the discovery of the genetic basis of anterior-posterior body patterning in bilaterian metazoans was the realization that Otx, Pax, and Hox genes are also expressed in a rostral to caudal sequence in those bilaterians that possess brains (90)(91)(92)(93)(94). This finding gave rise to the tripartite brain hypothesis, which proposes that there is a monophyletic origin of the brain in bilaterians.…”
Section: Comparative Approachesmentioning
confidence: 99%